Coparenting after marital dissolution and children's mental health: a systematic review - Lamela, Diogo (2016)
Research has shown that coparenting is a vital family mechanism in predicting mental health in children and adolescents. Considering the increasing prevalence of marital dissolution in Western societies, the objective of this systematic review was to summarize the key results of empirical studies that tested the association between mental health of children and coparenting after marital dissolution.